Pengenalan dan Penyerahan Tanaman Obat untuk Apotek Hidup pada Masyarakat RT. 009/RW. 012 Kelurahan Pondok Petir, Kecamatan Bojongsari, Kota Depok - Sumiahadi, Ade; Wijanarko, Citra Calista; Al Fajri, Agil Thoriq Bramantio; Ahmad, Nuhairan; Prabana, Rayi; Putri, Dirgahani; Wulandari, Yukarie Ayu; Maruf, Mohammad Ainul; Gustia, Helfi; Rosdiana, Rosdiana (STIE Pelita Nusantara, 2024)
Utilization of abandoned land to cultivate medicinal plants as a living pharmacy can independently meet the needs of the family's herbal medicines. The majority of people in the area of RT. 009/012 Kompleks Villa Pamulang, Pondok Petir Village, Bojongsari District, Depok City, still relies on chemical drugs and rarely uses herbal medicines. This is due to the people's lack of knowledge regarding the benefits of medicinal plants. Based on these conditions, the partner community hopes that there will be activities to introduce more herbal medicinal plants in creating healthy pharmacies in their environment. This community service activity aimed to introduce various medicinal plants and increase the availability of medicinal plants in living pharmacies in RT. 009/012 Kompleks Villa Pamulang. The activity was carried out at RT. 009/012 Kompleks Villa Pamulang, Pondok Petir Village, Bojongsari District, Depok City on 5-6 of August 2023. The activity consisted of two stages, namely, the explanation of medicinal plants and their benefits and the handing over of several types of medicinal plants to the people of RT. 009/012 Komleks Villa Pamulang. The activity went well and received great enthusiasm and response from the partner community. The partner community was delighted with the activities and gave a satisfaction rating of 92.5%. Partner community hopes there will be more activities related to environmental management and living pharmacies in the future.